Concentration dependent effect of calcium on brain mitochondrial bioenergetics and oxidative stress parameters - Pandya, Jignesh D.; Nukala, Vidya N.; Sullivan, Patrick G. (Frontiers in Neuroenergetics, 2013)
Mitochondrial dysfunction following traumatic brain and spinal cord injury (TBI and SCI) plays a pivotal role in the development of secondary pathophysiology and subsequent neuronal cell death. Previously, we demonstrated a loss of mitochondrial bioenergetics in the first 24 h following TBI and SCI initiates a rapid and extensive necrotic event at the primary site of injury. Within the mitochondrial derived mechanisms, the cross talk and imbalance amongst the processes of excitotoxicity, Ca2+ cycling/overload, ATP synthesis, free radical production, and oxidative stress damage ultimately leading to mitochondrial damage followed by neuronal cell death and loss of behaviors. Mitochondria are one of the most important organelles that regulate for intracellular calcium (Ca2+) homeostasis; and are equipped with a tightly regulated Ca2+ transport system. However, owing to the lack of consensus and the link between the downstream effects of calcium in published literature, we undertook a systematic in vitro study for measuring concentration dependent effects of calcium (100-1000 nmols/mg mitochondrial protein) on mitochondrial respiration, enzyme activities, reactive oxygen/nitrogen species (ROS/RNS) generation, membrane potential (∆Ψ) and oxidative damage markers in isolated brain mitochondria. We observed a dose- and time-dependent inhibition of mitochondrial respiration by calcium without influencing mitochondrial pyruvate dehydrogenase complex (PDHC) and NADH dehydrogenase (Complex I) enzyme activities. We observed dose-dependent decreased production of hydrogen peroxide and total ROS/RNS species generation by calcium and no significant changes in protein and lipid oxidative damage markers. These results may shed new light on the prevailing dogma of the direct effects of calcium on mitochondrial bioenergetics, free radical production and oxidative stress parameters that are primary regulatory mitochondrial mechanisms following neuronal injury.